The Effect of Anodic Oxidation Voltages on the Color and Corrosion Resistance of Commercially Pure Titanium (CP-Ti): - - Kandice Felisha Kurniawan; Ika Maria Ulfah; Muhammad Kozin (Journal of Evrímata: Engineering and Physics, 2023)
The effect of anodic oxidation (or anodizing) voltages on the color and corrosion resistance of pure titanium was studied. In this experiment, a commercially-pure titanium was used. To create an "illusion of color," anodizing process modified the oxide layer on the surface of titanium. Because of an interference effect similar to that of a prism, the titanium oxide layer gives the perception of color. Light reflects at different angles from the oxide layer and the underlying titanium, and these reflections interfere with each other. Certain wavelengths of light cancel or merge, resulting in the perception of color from the remaining light. It was concluded that when we use a higher voltage to anodize the titanium, the corrosion rate will increase. It was observed that using 10V gives us the most optimum resistance. For surface roughness, using 40V in both KOH and DAP solutions give us the highest roughness data. Due to the high amount of voltage used in anodizing the titanium, the coating got thicker in the surface and it affects the roughness. The data have shown that the corrosion rate and surface roughness were inversely proportional.